Estudo sobre o uso do pentacloreto de nióbio, como ácido de Lewis, na síntese de enaminas através da reação de adição de Michael - Trombini, Ana Paula Toledo [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The NbCl5 being a strong electrophile, is a potential candidate to act as a Lewis acid, and therefore it mediates various organic reactions. For this reason, it has received continuous attention by Brazilian researchers, especially in recent decades, since Brazil holds the largest reserves of niobium, besides being the largest producer of this element. The Michael addition reaction is one of the most widely used for forming carbon-carbon bonds and takes place by the addition of nucleophiles to activated olefins. Although this type of reaction is usually catalyzed by base, there are reports in the literature on the use of various Lewis acids in this type of reaction. The synthesis of enamines based acetilenodicarboxilates and amines, aromatic or alkyl, by Michael addition reaction is quite interesting, since these are valuable synthetic intermediates for the synthesis of heterocyclic and they are used in multicomponent reactions. The derivatives of anilino-fumarate also have a great potential for medical application. In this study we investigated the use of niobium pentachloride as Lewis acid to catalyze the Michael additions between the derivatives of aniline and acetilenodicarboxilates the synthesis of enamines

O NbCl5 sendo um eletrófilo forte, é um candidato em potencial para agir como ácido de Lewis, e portanto mediar várias reações orgânicas. Por esta razão, tem recebido contínua atenção por parte pesquisadores brasileiros, especialmente nas últimas décadas, uma vez que o Brasil é detentor das maiores reservas mundiais de nióbio, além de ser o maior produtor mundial desse elemento. A reação de adição de Michael é uma das reações mais utilizadas para a formação de ligações carbono-carbono e ocorre pela adição de nucleófilos a olefinas ativadas. Embora esse tipo de reação seja normalmente catalisada por base, há relatos na literatura sobre a utilização de diversos ácidos de Lewis neste tipo de reação. A síntese de enaminas baseadas em acetilenodicarboxilatos e aminas, aromáticas ou alquilicas, através da reação de adição de Michael é bastante interessante, pois estes são valiosos intermediários sintéticos para a síntese de heterocíclicos e utilização em reações multicomponentes. Os derivados de anilino-fumaratos também apresentam um grande potencial para aplicação na medicina. Neste trabalho investigamos o uso do pentacloreto de nióbio, como ácido de Lewis, em reações de adição de Michael entre derivados de anilina e acetilenodicarboxilatos na síntese de enaminas
Keywords: Quimica; Implantes artificiais; Catalisadores; Niobio; Chemistry